DISCUSS LANGUAGE AS A NATIONAL IDENTITY IN A MULTICULTURAL NATION: 1-SON 2-TO’PLAM IYUL 2023 yil - FerSU, 3 rd year student, Norinboeva Durdonakhon Janobiddin qizi; FerSU, 3rd year student, Ashurova O’g’ilchaxon G’olib qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Language plays a vital role in shaping national identities, particularly in multicultural nations. When a nation is home to diverse cultural groups and languages, the choice of language as a national identity becomes a complex and sensitive issue. This article will discuss the various aspects of language as a national identity in the context of a multicultural nation.